Massinissa Selmani: Bleu comme une Orange - Selmani, Massinissa (France; Art Collector, 2016)
Exhibition catalog. Sept 2016 @Selma Feriani Gallery.
French
Keywords: N4390-5098 Visual Arts- Exhibitions